Pattern of Mortality in Sudden Natural Death in North Delhi: A Prospective Autopsy Study (Medico Legal Update, 2019)
Objectives: In every population, the pattern of sudden natural deaths is often associated with the epidemiologicprofile of certain common killer diseases. The common belief has been that infectious/communicablediseases are the most common reasons of mortality. However, changing lifestyle, increasing literacy leveland advanced healthcare fascilities in India have impacted immensely on the causes of death. We, therefore,planned to determine the etiology and epidemiologic characteristics of sudden death at Hindurao hospital atNorth Delhi. The high incidence of sudden, unexpected death in the heart of the capital city is still an enigmaand hence we decided to analyse the cases of sudden death in the last two years at our hospital. This studywas conducted to illustrate etiolopathology, risk factors and triggers of sudden death with the aim to providenew insight in epidemiological aspects of sudden death. This should help in care of patients, and preventionof sudden death.Method: A prospective study of 124 cases of sudden death was conducted at a tertiary care hospital at NorthDelhi. After evaluating detailed history from the family members, autopsy has been performed to find outcause of sudden death.Results: The main etiology of sudden death is cardiovascular disease. Highest numbers of sudden deathare in old age group. Male patients succumbed to sudden death more which may be related to multiplecomorbidities in them. Sudden deaths were more encountered during winters and in morning hours. Thereare some autopsy negative cases, which are unexplained sudden death.Conclusions: Cardiovascular, respiratory disorders and central nervous system were the major causesof sudden natural death. Seasonal variation of sudden death especially from respiratory causes may beattributed to rise in pollution and poor air quality during winter season in Delhi.